KEBIJAKAN HUKUM PIDANA DALAM MEREHABILITASI NARAPIDANA ANAK - A.Latief Hasjim; Erniwati Erniwati (Fakultas Hukum Universitas IBA Palembang, 2020)
ABSTRACT Crime or crime does not limit gender and is not monopolized by adults or parents, in fact not even a small number of children are perpetrators of crime, which is generally